1993
DOI: 10.1097/00000658-199305010-00017
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Analysis of Diagnostic Laparoscopy in Trauma

Abstract: DL is a safe modality for trauma. With current technology, DL is most efficacious for evaluation of equivocal penetrating wounds. Significant cost savings would be gained by performance under local anesthesia. Development of miniaturized optics, bowel clamps, retractors, and stapling devices will reduce overall costs and permit some therapeutic applications for laparoscopy in trauma management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
125
0
12

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(145 citation statements)
references
References 19 publications
5
125
0
12
Order By: Relevance
“…[3] However, more recent reports have shown that 30-50% of all stab wounds do not penetrate the peritoneum and another 20-40% with peritoneal penetration do not involve significant injuries, resulting in non-therapeutic laparotomy rates as high as 70%. [1,4] Laparoscopy has recently been safely used for PAT patients for diagnostic and therapeutic purposes, avoiding unnecessary laparotomies, shortening the length of hospital stay, and reducing medical costs. [5,6] The aim of our study was to examine the use of diagnostic laparoscopy (DL) in the management of hemodynamically stable trauma patients with penetrating anterior abdominal injuries.…”
Section: Sonuçmentioning
confidence: 99%
“…[3] However, more recent reports have shown that 30-50% of all stab wounds do not penetrate the peritoneum and another 20-40% with peritoneal penetration do not involve significant injuries, resulting in non-therapeutic laparotomy rates as high as 70%. [1,4] Laparoscopy has recently been safely used for PAT patients for diagnostic and therapeutic purposes, avoiding unnecessary laparotomies, shortening the length of hospital stay, and reducing medical costs. [5,6] The aim of our study was to examine the use of diagnostic laparoscopy (DL) in the management of hemodynamically stable trauma patients with penetrating anterior abdominal injuries.…”
Section: Sonuçmentioning
confidence: 99%
“…[14,15,[21][22][23] Diagnostic laparoscopy is minimally invasive procedure that offers advantage of early detection and treatment of diaphragmatic injuries. [4,[6][7][8]17,21,24,25] Diaphragm injury rates have been reported in range of 10% to 50% in several studies that investigated left thoracoabdominal stab injuries using diagnostic laparoscopy. [1][2][3][4][5]8,22,26,27] In the present study, diaphragm injury rate was 23.5% in all patients and 22.1% in patients who underwent diagnostic laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis of diaphragm injury is difficult based on physical examination and imaging modalities, unless obvious signs and symptoms are present. [1][2][3][4][5][6][7][8] Thoracoabdominal region was defined as the area between the sternum, the fourth intercostal space, and the arcus costa anteriorly, and as the area between the vertebra, the inferior margin of the scapula and the last costal margin posteriorly. Region was divided into 3 subgroups: anterior (between the sternum and the anterior axillary line), lateral (between the anterior and posterior axillary lines) and posterior (between the posterior axillary line and the sternum).…”
Section: Introductionmentioning
confidence: 99%
“…Tension pneumothorax in patients with diaphragmatic injury from positive-pressure pneumoperitoneum [345,346]; gas embolism in patients with intra-abdominal venous injuries, especially in liver lacerations; and the transperitoneal absorption of carbon dioxide (which may cause metabolic and hemodynamic changes such as acidosis, cardiac suppression, atelectasis, subcutaneous emphysema, and increased intracranial pressure) might result in more profound and in some cases life-threatening consequences for the trauma patient and, as a consequence, clearly limits the potential indications for exploratory laparoscopy to a small number of very selected cases.…”
Section: Abdominal Traumamentioning
confidence: 99%